2019
DOI: 10.4274/mjima.2018.25
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem-resistant Acinetobacter baumannii in Adult Intensive Care Units: Risk Factors for Colonization and Infection

Abstract: Giriş: Karbapenem dirençli Acinetobacter baumannii (KDAB) izolatları yoğun bakım ünitelerinde (YBÜ) ciddi tehditlerdendir. Bu çalışmada yetişkin yoğun bakım hastalarında KDAB kolonizasyonu ve enfeksiyonu ile ilişkili risk faktörlerinin araştırılması amaçlanmıştır. Gereç ve Yöntem: Cerrahi/medikal YBÜ'de 48 saatten fazla hastaneye yatırılan hastalar KDAB edinimi için tarandı. Çevre kültürleri alındı. Tanımlama ve antibiyotik duyarlılığı Vitek 2 (bioMérieux, Fransa) ile belirlendi. bla OXA-23 , bla OXA-40 , bla … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…It was evident that the mortality risk factors in patients with hospital-acquired infections caused by CRAB were exposure to IMV, having been treated in other hospital units, and having been medicated with carbapenems. At the public hospital of Turkey, the risk factors of Acinetobacter baumannii resistance to infection with carbapenems found in the analysis showed that the use of IMV had a rank of p = 0.016; stays shorter than 15 days in the ICU had a rank of p < 0.001; and a history of using carbapenems had a rank of p < 0.001, among other independent risk factors [ 34 ]. The multicenter study carried out in Turkey showed that long-term supply of drugs at the ICU, bacteremia associated with ventilation, use of third-generation cephalosporins before the diagnosis of an infection, and liver cirrhosis were important risk factors in the mortality of patients infected with Acinetobacter baumannii [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was evident that the mortality risk factors in patients with hospital-acquired infections caused by CRAB were exposure to IMV, having been treated in other hospital units, and having been medicated with carbapenems. At the public hospital of Turkey, the risk factors of Acinetobacter baumannii resistance to infection with carbapenems found in the analysis showed that the use of IMV had a rank of p = 0.016; stays shorter than 15 days in the ICU had a rank of p < 0.001; and a history of using carbapenems had a rank of p < 0.001, among other independent risk factors [ 34 ]. The multicenter study carried out in Turkey showed that long-term supply of drugs at the ICU, bacteremia associated with ventilation, use of third-generation cephalosporins before the diagnosis of an infection, and liver cirrhosis were important risk factors in the mortality of patients infected with Acinetobacter baumannii [ 30 ].…”
Section: Discussionmentioning
confidence: 99%